Effect of welding speed on microstructure and corrosion resistance of Al–Li alloy weld joint. Issue 2 (14th August 2019) - Yang, Mei; Lu, Jingxiang; Chen, Jing; Li, Yang; Liu, Yang; Yang, Honglang
Abstract: The corrosion resistance of a weld has a great impact on the service life of the joint. Changes in welding parameters can cause changes to the heat input, which affect the formation of the weld bead and the precipitation of the second phase, which determines the corrosion resistance of the weld. In this paper, the effect of a change in the welding speed on 2195 aluminium–lithium (Al–Li) alloy joints welded by laser and metal inert gas (laser‐MIG) hybrid welding using Al–Si welding wire was studied. The macrostructure and microstructure of the weld were characterized by optical microscopy, X‐ray diffraction, and scanning electron microscopy. The results show that the predominant precipitates in the laser‐MIG hybrid welded Al–Li alloy were the θ (Al2 Cu) and T (Al–Li–Si) phases. As the welding speed increased from 11.5 mm/s to 16.5 mm/s, the heat input decreased, and the amount of the precipitated phase increased. Intergranular corrosion and electrochemical experiments were carried out on the weld seam, and the corrosion resistance was tested. With increasing welding speed, the corrosion resistance of the weld decreased. The high potential of the precipitated phase decreased the corrosion resistance of the weld joint. Abstract : Changes in welding parameters can cause changes in the heat input which will affect the formation of the weld bead and the precipitation of the second phase, which determines the corrosion resistance of the weld. The 2195 aluminum–lithium alloy is welded at different welding speed. The effect of welding speed on weld corrosion resistance was tested.